Beyond bad apples, toward Black life: A re-reading of the implicit bias research. (November 2019) - Petersen, Amanda M
Increasingly, the death of Black individuals at the hands of the US legal system is interpreted in relation to the social science research on implicit bias. Having flourished in the past decade, this oft-cited framework for recognizing and eliminating anti-Blackness not only overwhelms the socio-legal and criminological scholarship, but also pervades political discourse and popular culture. Using as a site of study my own empirical research on implicit bias and Oregon prison sentences, I discuss problems related to the study of implicit bias and legal outcomes in the social sciences. Further, I examine common understandings of implicit bias research and the troubling application of these knowledges to legal policies and practices. In interrupting the current fascination with and use of implicit bias research, I turn toward "abolitionist pedagogy" in my interpretation of empirical evidence.